Pole-to-Pole Connections: Similarities between Arctic and Antarctic Microbiomes and Their Vulnerability to Environmental Change - Kleinteich, Julia; Hildebrand, Falk; Bahram, Mohammad; Voigt, Anita Y.; Wood, Susanna A.; Jungblut, Anne D.; Küpper, Frithjof C.; Quesada, Antonio; Camacho, Antonio; Pearce, David A.; Convey, Peter; Vincent, Warwick F.; et al. (Frontiers in Ecology and Evolution, 2017)
The global biogeography of microorganisms remains poorly resolved, which limits the current understanding of microbial resilience towards environmental changes. Using high-throughput 16S rRNA gene amplicon sequencing, we characterized the microbial diversity of terrestrial and lacustrine biofilms from the Arctic, Antarctic and temperate regions. Our analyses suggest that bacterial community compositions at the poles are more similar to each other than they are to geographically closer temperate habitats, with 32 % of all operational taxonomic units (OTUs) co-occurring in both polar regions. While specific microbial taxa were confined to distinct regions, representing potentially endemic populations, the percentage of cosmopolitan taxa was higher in Arctic (43 %) than in Antarctic samples (36 %). The overlap in polar microbial OTUs may be explained by natural or anthropogenically-mediated dispersal in combination with environmental filtering. Current and future changing environmental conditions may enhance microbial invasion, establishment of cosmopolitan genotypes and loss of endemic taxa.